2019
DOI: 10.1177/1090198118825236
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Hopeful Motivates Change: Emotional Responses to Messages Communicating Comparative Risk of Electronic Cigarettes and Combusted Cigarettes

Abstract: Background: Emotions are important in smoking-related communications, but the role of discrete positive and negative emotions in comparative risk messages about combusted and electronic cigarettes (e-cigarettes) is unclear. Method: In an online experiment, 1,202 U.S. adult current smokers or recent quitters were randomized to view one of six messages about comparative risk of e-cigarettes and cigarettes. Participants reported their feelings of hope, happiness, fear, guilt, disgust, and anger and risk percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…After removal of duplicates and publications that did not meet the inclusion criteria, a total of 31 articles were included [7,8,24–28,34–57] (Table 3) reporting results from studies involving a total of 52 425 participants (ranging from 95–16 051). Twenty‐six of the included studies were experiments and the remaining were cross‐sectional surveys.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removal of duplicates and publications that did not meet the inclusion criteria, a total of 31 articles were included [7,8,24–28,34–57] (Table 3) reporting results from studies involving a total of 52 425 participants (ranging from 95–16 051). Twenty‐six of the included studies were experiments and the remaining were cross‐sectional surveys.…”
Section: Resultsmentioning
confidence: 99%
“…When combined with a nicotine fact sheet, CR messages produced higher levels of response efficacy and produced higher odds of people disagreeing with the false statement that nicotine is the main cause of smoking‐related health problems compared to the other CR messages [35]. A nicotine fact sheet alone also corrected misperceptions of nicotine and NVPs compared with control or no message conditions [37,53].…”
Section: Resultsmentioning
confidence: 99%
“…Themes of unity and diversity were desired across all focus groups. Prior studies have shown that messages evoking both negative (e.g., fear) and positive (e.g., hope) emotions can elicit beneficial behavior changes [ 27 , 28 ], so future research should examine these possibilities in the context of messages to promote face coverings. More research into the language that resonates with specific communities is needed, especially considering the inequities in COVID-19 morbidity and mortality among underserved minority populations [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These emotions can be particularly relevant to smokers because smoking-related COVID-19 disease information possibly conjures up the prospect of severe complications. Research has found that exposure to smoking disease information may arouse similar emotions for smokers [ 26 ]. However, smoking disease likely represents a chronic threat to smokers due to their prolonged exposure to anti-smoking information, and thus, the threat might be perceived as normal and distant in time [ 9 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ATF, however, argues that emotions have different associations with cognitive appraisals and themes, which determine individuals’ judgments and choices [ 36 ]. Using the ATF, Yang et al [ 26 ] found that messages communicating the risk of smoking cigarettes aroused higher fear, guilt, disgust, hope, and anger. The first four emotions were associated with higher intentions to quit smoking, seek quit help, use nicotine replacement therapy (NRT), switch to e-cigarettes, and use e-cigarettes exclusively.…”
Section: Introductionmentioning
confidence: 99%